Laboratory-AE-driven wavelet-enhanced CNN for in-situ microseismic recognition - Zhizhong Jiang; Jinhui Li; Zhijie Wen; Longjun Dong; Zhenqian Ma; Shaojie Zuo; Yu Liu; Zhichao Zhang; Haowei Tian (International Journal of Rock Mechanics and Mining Sciences, 2026)

Antibacterial mechanisms of magnolol against Streptococcus agalactiae and immunomodulatory effects in Schizothorax prenanti - Yilin Wang; Kun Peng; Longjun Deng; Yihao Wang; Qibin Jiang; Tiancai Li; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2026)

Myostatin in fish: current understanding of its characterization, function, and signaling pathways - Yujun Wang; Longjun Deng; Tiancai Li; Li Liu; Dongjie Wang; Wei Luo; Zongjun Du (Fish Physiology and Biochemistry, 2026)

The increasing impact of vegetation productivity on global wetland methane emissions - Longjun Wang; Peng Li; Qiuan Zhu; Xiaolu Zhou; Zhengmiao Deng; Zelin Liu; Ziying Zou; Changhui Peng (Global and Planetary Change, 2026)

Life-cycle regulation of carbohydrate metabolism revealed by glucokinase (gck) in two cyprinids, Spinibarbus denticulatus and Schizothorax prenanti - Yongyao Guo; Yue Zhang; Tiancai Li; Longjun Deng; Zhonggang Guo; Li Liu; Pengyu Chen; Luojia Li; Wei Luo; Dongjie Wang; Zongjun Du (Aquaculture, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Research on microseismic parameter prediction for rock mass instability disasters based on time series models - Longjun Dong; Xiaofeng Huang; Shenglan Li; Jiachuang Wang (Journal of Applied Geophysics, 2026)

Electro-chemo-mechanically stable semi-interpenetrating interphase customization for prolonged Zn metal anodes - Jianhui Zhu; LongJun He; Jianbin Ruan; Hongying Li; Chenglong Xu; Ming Yang; Guomin Li; Yanyi Wang; Jingting Luo; Jinlai Zhao; Dingtao Ma; Peixin Zhang (Chemical Engineering Journal, 2026)

Degradable Janus structured micro-nano fibrous membranes for effective particle filtration and antibacterial activity in high humidity working conditions - Gang Zhou; Zhuo Xu; Gang Li; Longjun Wang; Heng Sun; Mingyu Zhang; Yueying Xin; Yongmei Wang (Chemical Engineering Journal, 2026)

Overexpression of PbWRKY66 negatively regulate phosphate uptake and root-to-shoot distribution in Arabidopsis - Mengdan Li; Wenyu Sun; Mengjie Wu; Fangyan Li; Zhen Cao; Nian Liu; Longjun Cheng (Plant Science, 2026)

Editor's Note to “Wastewater inputs reduce the CO2 uptake by coastal oceans” [Sci. Total Environ., 901 (2023), 165700] - Yunxiao Li; Liang Xue; Xufeng Yang; Ming Xue; Ping Han; Xiangyu Liu; Han Zang; Pengjin Yang; Wei-Jun Cai; Longjun Zhang (Science of The Total Environment, 2026)

Wake-induced vibration of a downstream cylinder in tandem configurations: an activation-modulation framework - Qiuying Li; Guanghao Chen; Nan Jiang; Jinhui Yue; Longjun Wang; Jian Liu (Ocean Engineering, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Responses of viral communities and viral-encoded auxiliary metabolic genes to long-term fertilization practices under different land-use types - Xunqi Chen; Dong Zhu; Yuling Zheng; Xiaomin Li; Guoxin Sun; Xiaoming Li; Longjun Ding (Journal of Environmental Sciences, 2026)

Measurement and Impact Mechanism of Carbon Costs in China’s Industrial Enterprises - Liping Wang; Longjun Chen; Panpan Gao; Chuang Li (Environmental Modeling & Assessment, 2026)

Evaluating rock instability risk areas in deep mining using microseismic monitoring-based risk fields - Fang Yan; Shengnan Du; Longjun Dong; Xuan Li; Guanguan Li; Feifan He (Journal of Mountain Science, 2026)

Real-time wave velocity evolution and thermal damage development in hollow-sphere granite: Insights from progressive heating experiments - Zixin Huang; Qiaomu Luo; Longjun Dong; Longbin Yang; Shenglan Li; Xuewei Li (Journal of Applied Geophysics, 2026)

Ammonia nitrogen accumulation and metabolic regulation in large-scale loach (Paramisgurnus dabryanus) exposed to sub-chronic carbonate alkalinity: Insights from biochemical and omics analyses - Wei Luo; Luojia Li; Li Liu; Yujun Wang; Longjun Deng; Tiancai Li; Dongjie Wang; Zongjun Du (Aquaculture, 2026)

Study on the Bioavailability of Arsenic in the Rice–Crayfish Farming System - Kelei Zhang; Shoudong Zhang; Longjun Deng; Tiancai Li; Li Liu; Wei Luo; Yibo Zhang; Yongyao Guo; Dan Liu; Shiyong Yang; Jun Wang; Dongjie Wang; et al. (Fishes, 2025)
Rice–fishery integrated farming has expanded rapidly in China, yet its implications for arsenic (As) accumulation remain insufficiently understood. This study evaluated As bioavailability and enrichment in a rice–crayfish farming system (RCFS) by establishing controlled field plots with soil As concentrations ranging from 5 to 40 mg/kg under three water-management regimes: alternating wetting and drying (AWD), continuously flooded (CF), and RCFS. Soil–water physicochemical variables and As accumulation in both rice organs and crayfish tissues were systematically analyzed, followed by human health risk assessment. Inorganic As in brown rice increased linearly with soil As, following Y = 0.0117X + 0.0598 (R2 = 0.96), and the estimated soil safety thresholds were 26.48 mg/kg for AWD, 11.98 mg/kg for RCFS, and 9.24 mg/kg for CF. AWD consistently exhibited the lowest As risk due to its ability to elevate soil Eh and maintain a more favorable pH, thereby suppressing As mobilization. Compared with CF, RCFS reduced As bioavailability through crayfish-induced bioturbation, which increased Eh, enhanced SOM and CEC, and improved soil aeration. As accumulation in crayfish tissues also rose with soil As, with abdominal muscle As fitting Y = 0.0085X + 0.0553 (R2 = 0.8588). Although abdominal muscle met safety limits, the hepatopancreas accumulated substantially higher As and exceeded carcinogenic risk thresholds, even at 5 mg/kg of soil As, indicating a potential health concern for consumers. This work elucidates As dynamics and enrichment mechanisms in RCFS, providing guidance for safer rice–crayfish production in As-impacted areas.

The C2H2 Zinc-Finger protein ELR1 negatively regulates cytokinin metabolism and signaling pathway in rice - Zeyu Li; Shuyi He; Longjun Zeng; Guangzhong Zhang; Quan Wang (Functional & Integrative Genomics, 2025)

Superhydrophilic adsorptive nanofiber membranes for ultrafast and highly-efficient waterborne nanoplastic removal - Jingwen Zhou; Mi Zhou; Longjun Wang; Jiayu Tong; Xinhao Li; Jingru Zhou; Yuqian He; Linlin Yan; Xiquan Cheng (Journal of Hazardous Materials, 2025)

How to improve enterprises’ responsiveness to green policies? Empirical evidence from multivariate policy scenario analysis - Liping Wang; Longjun Chen; Ting Zeng; Chuang Li (Environment, Development and Sustainability, 2025)

Modelling the impacts of climate change and harvesting on carbon dynamics in representative subtropical secondary forests: A case study from Hunan Province, China - Longjun Wang; Haoyun Liu; Zelin Liu; Tong Li; Peng Li; Ziying Zou; Xiaolu Zhou; Weifeng Wang; Changhui Peng; Wenhua Xiang; Cong Liu (Ecological Modelling, 2025)

High-density magnetic-carbon interfaces in NiCu@C heterojunction toward broadband electromagnetic wave absorption - Zhikai Yan; Mengqiu Huang; Longjun Rao; Wenbin You; Biao Zhao; Lei Wang; Limin Wu; Ruixuan Zhang; Wei Li; Renchao Che (Chemical Engineering Journal, 2025)

A comprehensive understanding of thermal tolerance in Percocypris pingi (Tchang, 1930) under different acclimation temperatures supported by behavioral assessments - Yongyao Guo; Tong Li; Li Liu; Tiancai Li; Longjun Deng; Siyi Zhu; Shun Zhong; Qingjie Wang; Dongjie Wang; Wei Luo; Zongjun Du (Journal of Thermal Biology, 2025)

Human-machine-environment temperature field monitoring and analysis in deep high-temperature mining areas - Qiaomu Luo; Naiping Li; Longjun Dong; Hongmei Shu (Journal of Mountain Science, 2025)

Development of cell labeling and gene editing tools in urochordate Ciona - Xiang Li; Lu Mu; Hongzhe Peng; Sun Nyunt Wai; Longjun Pu; Bo Dong (Marine Life Science & Technology, 2025)
Urochordate Ciona spp. are ideal marine model organisms for studying embryogenesis and developmental and evolutionary biology. However, the effective implementation of genetic labeling and CRISPR/Cas9-based editing tools at cellular resolution remains challenging. This study successfully developed and validated a collection of Gateway-based vectors for cell labeling in Ciona spp. The destination vector sets contained two Gateway cassettes flanked by Minos sites, allowing the N- or C-terminal tagging of a protein of interest with various fluorescent markers. In addition, we optimized the CRISPR/Cas9 and CRISPR/dCas9 systems by incorporating P2A-mCherry, a fluorescent indicator for Cas9 expression at cellular resolution. We demonstrated the effective destruction or inhibition of target genes when CRISPR constructs were introduced into fertilized eggs. Furthermore, we engineered a dual fluorescence sensor system that helps visualize successful gene knockouts at the cellular level in specific tissues. The genetic tools developed in this study offer a robust method for gene expression, cell tracking, and subcellular protein localization while also facilitating tissue-specific functional analysis in Ciona embryos and other model systems.

Knockout of the Staphylococcus aureus virulence gene sdrC promotes Myh7 expression to inhibit the progression of osteomyelitis - Baochuang Qi; Lili Yang; Xinyu Fan; Dongdong Qin; Jiming Gan; Tao Chen; Yu Rao; Zhongyu Peng; Longjun Su; Chuan Li; Yongqing Xu (Journal of Molecular Histology, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

Computational Analysis of Fault-Slip Induced Strainburst Using Strain Energy Density - Seun A. Ajayi; Longjun Dong; Xiaofeng Huang; Daoyuan Sun; Shenglan Li (Geotechnical and Geological Engineering, 2025)

A Pyrene-Derived Fluorescent Probe for the Visual Detection of Protamine and Trypsin Activity - Longjun Xiong; Yutian Jiao; Yu Liu; Gongli Wei; Baocai Xu; Fu Han; Li Zhao (Journal of Fluorescence, 2025)

Measurement and Stress Response Analysis of Complete History of Blast-Induced Wall Pressure for Boreholes: A Case with Air-Deck Charge - Qiyue Li; Xinao Wei; Xibing Li; Kai Liu; Longjun Dong; Ming Tao; Haiqian Li (Rock Mechanics and Rock Engineering, 2024)

Engineering human midbrain organoid microphysiological systems to model prenatal PFOS exposure - Chunhui Tian; Hongwei Cai; Zheng Ao; Longjun Gu; Xiang Li; Vivian C. Niu; Maria Bondesson; Mingxia Gu; Ken Mackie; Feng Guo (Science of The Total Environment, 2024)

Exploring the spatial relationship between soil quality index and soil ecosystem services driven by social-ecological factors: A peri-urban case study in central China - Jiaxin Guo; Guangyu Li; Qing Zhu; Yefeng Jiang; Xi Guo; Longjun Ding; Xiaomin Zhao (CATENA, 2024)

Spatio-temporal evolution characteristics and spatial spillover effects of forest carbon sink efficiency in China - Liping Wang; Longjun Chen; Ying Long; Chuang Li (Environment, Development and Sustainability, 2024)

Enhanced reaction kinetics and structure integrity of Cu/F co-doped SnO2@C composite for high-performance lithium-ion batteries - Shixin Huang; Longjun Guo; Wei Liu; Chunjin Hang; Rong An; Yongfeng Li; Yanhong Tian (Chemical Engineering Journal, 2024)

Osteoarthritis rat serum-derived extracellular vesicles aggravate osteoarthritis development by inducing NLRP3-mediated pyroptotic cell death and cellular inflammation - Zhifang Tang; Longjun Shu; Zijian Cao; Yongqing Xu; Chuan Li (Human Cell, 2024)

Correction: FTY720 Inhibits MPP+-Induced Microglial Activation by Affecting NLRP3 Inflammasome Activation - Shu Yao; Longjun Li; Xin Sun; Jun Hua; Keqi Zhang; Li Hao; Lixin Liu; Dongyan Shi; Hong Zhou (Journal of Neuroimmune Pharmacology, 2024)

In situ mass spectrometry imaging reveals pesticide residues and key metabolic pathways throughout the entire cowpea growth process - Shufan Jiang; Jingling Lin; Rui Zhang; Qiong Wu; Hongxing Li; Qun Zhang; Mingyue Wang; Longjun Dai; Defang Xie; Yue Zhang; Xinzhong Zhang; Bingjun Han (Journal of Hazardous Materials, 2024)

Divergent contributions of spring and autumn photosynthetic phenology to seasonal carbon uptake of subtropical vegetation in China - Ying Peng; Peng Li; Xiaolu Zhou; Yunpeng Luo; Cicheng Zhang; Longjun Wang; Tong Li; Changhui Peng (Journal of Geographical Sciences, 2024)

Heterointerface engineering in porous microspheres for magnetic-dielectric balance to boost electromagnetic wave absorption - Longjun Rao; ZhuoLin Li; Yuetong Qian; Mengqiu Huang; Lei Wang; Yongsheng Liu; Jincang Zhang; Yuxiang Lai; Chongyun Liang; Renchao Che (Chemical Engineering Journal, 2024)

Genotype diversity and antibiotic resistance risk in Aeromonas hydrophila in Sichuan, China - Kun Peng; Mengzhu Chen; Yilin Wang; Ziqi Tian; Longjun Deng; Tiancai Li; Yang Feng; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Brazilian Journal of Microbiology, 2024)

miRNA-146a-5p Inhibits Hypoxia-Induced Myocardial Fibrosis Through EndMT - Yan Wang; Jie Yu; Chunxia Ou; Yue Zhao; Lixing Chen; Wenke Cai; Huawei Wang; Shiying Huang; Jie Hu; Guihu Sun; Longjun Li (Cardiovascular Toxicology, 2024)

IFITM3 restricts porcine deltacoronavirus infection by targeting its Spike protein - Jianxiao Wu; Rongfeng Tang; Xiaorong Zhang; Mingzhe Gao; Longjun Guo; Liaoyuan Zhang; Da Shi; Xin Zhang; Hongyan Shi; Hongying Song; Li Feng; Jianfei Chen (Veterinary Microbiology, 2024)

Probabilistic seismic capacity models for circular tunnels at different performance levels - Longjun Xu; Jingzhou Zhu; Guochen Zhao; Shuang Li (Computers and Geotechnics, 2024)

The MPK6-LTF1L1 module regulates lignin biosynthesis in rice through a distinct mechanism from Populus LTF1 - Ping Zhu; Yu Zhong; Laifu Luo; Junhui Shen; Jiayan Sun; Laigeng Li; Longjun Cheng; Jinshan Gui (Plant Science, 2023)

Gill structure and respiratory ability of Euchiloglanis kishinouyei (Osteichthyes: Siluriformes: Sisoridae) - Luojia Li; Longjun Deng; Jie Li; Tiancai Li; Pengyu Chen; Wei Luo; Zongjun Du (Journal of Fish Biology, 2023)
Glyptosternoid fishes are distributed in the torrent environment of alpine canyons, where they often leave the water to climb rocky cliffs. As one of the most primitive species of glyptosternoid fishes, Euchiloglanis kishinouyei was examined in the current study to analyse its gill microstructure and respiratory ability. We first found that the oxygen consumption rate was relatively high and negatively correlated with body mass and that the average oxygen consumption at night was higher than during the day. The asphyxiation point of E. kishinouyei (5.05 ± 0.22 g) was c . 1.93 mg/L. Subsequently, the surface morphology, gross gill tissue structure, and ultra‐microstructure of gill lamellae were investigated using optical microscopy and SEM. The gills showed an overall trend of regression, with five pairs of gill arches in each gill cavity. The adjacent gill filaments had large gaps, and the gill lamellae were thick. The gill filaments were closely arranged on the gill arches, their folded respiratory surface was highly vascularized with no tiny crest, and there were obvious tiny crests, grooves, pits, and pores on the nonrespiratory surface. The gill lamellae were closely embedded on both sides of gill filaments, which were composed of flat epithelial cells, basement membrane, pillar cells, and mucous cells. The gill total respiratory area correlated positively with body mass and length, whereas the gill relative respiratory area correlated negatively with body mass. We comprehensively analysed the gill microstructure and respiratory capacity of E. kishinouyei to provide fundamental data for the adaptive evolution of the gill structures of bimodally respiring fishes and offer insights into further study on the accessory air‐breathing function of skin.

Wastewater inputs reduce the CO2 uptake by coastal oceans - Yunxiao Li; Liang Xue; Xufeng Yang; Qinsheng Wei; Ming Xin; Ming Xue; Chenhua Han; Ping Han; Xiangyu Liu; Han Zang; Pengjin Yang; Xiangbin Ran; et al. (Science of The Total Environment, 2023)

Grazing alters vegetation phenology by regulating regional environmental factors on the Tibetan Plateau - Longjun Wang; Peng Li; Tong Li; Xiaolu Zhou; Zelin Liu; Ziying Zou; Qiuan Zhu; Changhui Peng (Agriculture, Ecosystems & Environment, 2023)

Visualization and metabolome for the migration and distribution behavior of pesticides residue in after-ripening of banana - Meiran Wang; Qiaoxia Tian; Hongxing Li; Longjun Dai; Yi Wan; Mingyue Wang; Bingjun Han; Huaping Huang; Yunuo Zhang; Juncheng Chen (Journal of Hazardous Materials, 2023)

High resistance to Ichthyophthirius multifiliis in Percocypris pingi, an endemic fish in upper Yangtze River - Linzhu Li; Maohua Li; Rukui Zeng; Longjun Deng; Kun Yang; Zhaobin Song (Aquaculture, 2023)

Comparative transcriptome and adaptive evolution analysis on the main liver and attaching liver of Pareuchiloglanis macrotrema - Qing Wu; Xiaoyang Zhang; Jie Li; Longjun Deng; Dongjie Wang; Min Liao; Zhonggang Guo; Xiaoli Huang; Defang Chen; Yan Wang; Shiyong Yang; Zongjun Du; et al. (Journal of Applied Genetics, 2022)

FTY720 Inhibits MPP+-Induced Microglial Activation by Affecting NLRP3 Inflammasome Activation - Shu Yao; Longjun Li; Xin Sun; Jun Hua; Keqi Zhang; Li Hao; Lixin Liu; Dongyan Shi; Hong Zhou (Journal of Neuroimmune Pharmacology, 2019)

Focal Mechanism of Mining-Induced Seismicity in Fault Zones: A Case Study of Yongshaba Mine in China - Ju Ma; Longjun Dong; Guoyan Zhao; Xibing Li (Rock Mechanics and Rock Engineering, 2019)

Qualitative Method and Case Study for Ground Vibration of Tunnels Induced by Fault-Slip in Underground Mine - Ju Ma; Longjun Dong; Guoyan Zhao; Xibing Li (Rock Mechanics and Rock Engineering, 2019)

An Improved P-Phase Arrival Picking Method S/L-K-A with an Application to the Yongshaba Mine in China - Xueyi Shang; Xibing Li; A. Morales-Esteban; Longjun Dong (Pure and Applied Geophysics, 2018)

Characterization of porcine epidemic diarrhea virus infectivity in human embryonic kidney cells - Jian Zhang; Longjun Guo; Yunfei Xu; Lijun Yang; Hongyan Shi; Li Feng; Yue Wang (Archives of Virology, 2017)

Molecular cloning and expression analysis of the mevalonate diphosphate decarboxylase gene from the latexof Hevea brasiliensis - Chuntai Wu; Yu Li; Zhiyi Nie; Longjun Dai; Guijuan Kang; Rizhong Zeng (Tree Genetics & Genomes, 2017)

Dynamic Brazilian Splitting Test of Ring-Shaped Specimens with Different Hole Diameters - Xibing Li; Qiuhong Wu; Ming Tao; Lei Weng; Longjun Dong; Yang Zou (Rock Mechanics and Rock Engineering, 2016)

Production of porcine TNFα by ADAM17-mediated cleavage negatively regulates porcine reproductive and respiratory syndrome virus infection - Ren Li; Longjun Guo; Weihong Gu; Xiaolei Luo; Jian Zhang; Yunfei Xu; Zhijun Tian; Li Feng; Yue Wang (Immunologic Research, 2016)

Three-dimensional water quality model based on FVCOM for total load control management in Guan River Estuary, Northern Jiangsu Province - Li Zhang; Weibo Lin; Keqiang Li; Jianming Sheng; Aihong Wei; Feng Luo; Yan Wang; Xiulin Wang; Longjun Zhang (Journal of Ocean University of China, 2016)

TNP-ATP is Beneficial for Treatment of Neonatal Hypoxia-Induced Hypomyelination and Cognitive Decline - Jie Xiao; Yilong Huang; Xia Li; Longjun Li; Ting Yang; Lixuan Huang; Ling Yang; Hong Jiang; Hongchun Li; Fan Li (Neuroscience Bulletin, 2016)

Discrimination of Mine Seismic Events and Blasts Using the Fisher Classifier, Naive Bayesian Classifier and Logistic Regression - Longjun Dong; Johan Wesseloo; Yves Potvin; Xibing Li (Rock Mechanics and Rock Engineering, 2016)

Quantitative trait locus analysis and fine mapping of the qPL6 locus for panicle length in rice - Lin Zhang; Jianjun Wang; Junmin Wang; Linyou Wang; Bin Ma; Longjun Zeng; Yongbin Qi; Qun Li; Zuhua He (Theoretical and Applied Genetics, 2015)

In-depth proteome analysis of the rubber particle of Hevea brasiliensis (para rubber tree) - Longjun Dai; Guijuan Kang; Yu Li; Zhiyi Nie; Cuifang Duan; Rizhong Zeng (Plant Molecular Biology, 2013)

Carbonate mineral saturation states along the U.S. East Coast - Li-Qing Jiang; Wei-Jun Cai; Richard A. Feely; Yongchen Wang; Xianghui Guo; Dwight K. Gledhill; Xinping Hu; Felipe Arzayus; Feizhou Chen; Justin Hartmann; Longjun Zhang (Limnology and Oceanography, 2010)
To assess the impact of ocean acidification on the carbonate chemistry of the shelf waters off the southeastern United States (South Atlantic Bight [SAB]), we measured carbonate mineral saturation states from January 2005 to May 2006. The findings reveal that aragonite (Ω arag : 2.6–4.0) and calcite (Ω cal : 4.1–6.0) saturation states were considerably higher than those recently reported along the West Coast of North America. Different water mass age between the Atlantic and Pacific Oceans during global ocean circulation is the primary reason for the higher carbonate mineral saturation states in the SAB than along the West Coast. The contrasting water temperatures in the two coasts contribute to such differences. Both upwelling and freshwater discharge also play important roles in controlling saturation state. Carbonate mineral saturation in the surface water of the West Coast is strongly controlled by the upwelling of high‐salinity, low‐temperature, low‐oxygen, and low‐pH deep water. In comparison, saturation states in the surface water of the SAB coast are rarely affected by upwelling. Instead, they are strongly influenced by the input of low‐saturation‐state water from rivers. Continued increases of atmospheric CO 2 under the Intergovernmental Panel on Climate Change B1 emission scenario will decrease the carbonate mineral saturation states by up to 40% by the end of this century, and aragonite will approach undersaturation near the coast.